Cross-strain Analysis of Impulsivity - Yanagita, Bryan T.; McGrath, Shawn R.; Boley, Chance A. (My University, 2014)
Delay discounting is a term that describes how the value of an outcome decreases as its receipt is delayed over time. This effect can be assessed by exposing subjects to repeated choices between a small reward delivered immediately versus a larger amount delivered after a delay. The purpose of this study was to compare delay discounting in two rat strains to evaluate cross-strain differences in impulsivity.
Color poster with text, graphs, tables, and charts.
Keywords: Impulse; Delay discounting; Posters